PERAN UNIT BINTIBMAS DALAM MENCEGAH TINDAK PIDANA KEKERASAN ANAK MELALUI BIMBINGAN DAN PENYULUHAN DI POLRESTA BOGOR KOTA - Mas Iqbal (Police Studies Review, 2020)
In the last year 2019 child violence is the highest case in the previous year with the amount of 76 cases, in the strengthen with interviews with Kanit PPA Polresta Bogor City IPTU Frida Hidayanti, S.H. on February 20, 2020 at 09.00 WIB which explains if: "for criminal acts of violence in children, namely covering cases of persecution and violence whether it is physical , psychic, or sexual in the Polresta Bogor City in the year 2019 number is as much as seventy six cases and is one of the highest in West Java. The binary units of the Bintibmas unit have a role in trying to cope with the child's violent case with guidance and counseling. This research aims to analyse and describe the efforts and factors affecting the implementation of guidance and counseling by the Bintibmas unit. Location of research in Polresta Bogor City with the focus of guidance and extension of the Bintibmas unit. This research uses qualitative methods with descriptive analysis techniques. Using Data trianggulation (Moleong; 2006:330) 4 (four) kinds of techniques, namely sources, theories and techniques and primary, secondary and tertiary data sources. Data-validity is data reduction, data feed, conclusion withdrawal and verification. This research uses the theory of management functions, the theory of management elements and the theory of Force Field Analyisys as well as the concept of roles, concepts of guidance and counseling, concept of child violence and the concept of bintibmas. Implementation of less maximum guidance and counseling conducted by the unit Bintibmas analyzed from the planning function of the preparation of materials determines the target of guidance and counseling, organizing is to prepare competent officers, implementation and control of assessment and monitoring in the activities of guidance and counseling. In the implementation of guidance and counseling there are internal factors that influence is the factors of people, budgets, infrastructure and methods of binluh and external factors that influence is public awareness and factors of other functions as well as efforts made in the form of a coaching path effort and efforts of relationships and procedures of work. The conclusion is that the mentoring and counseling factors conducted by the Bintibmas unit is the competency of members, counseling materials, budgets, cooperation with other functions and agencies, determination of BINLUH objectives and guidance and counseling methods. Keywords: role of Bintibmas Unit through guidance and counseling, child violence.